Solve for x.
7(3 - x) = 8(4 - 2x)
x = -53/23
x = -5/9
x = 11/23
x = 11/9

7(3 - x) = 8(4 - 2x) 7x+21= 16x+32 - 7x + 21 = 32 + 16x 9x + 21 = 32 9x = 32 - 21 9x = 11 x = 11/9

s

Question

Asked 10/5/2012 10:32:28 AM

Updated 10/10/2015 1:25:29 PM

1 Answer/Comment

Rating

3

7(3 - x) = 8(4 - 2x)

7x+21= 16x+32

- 7x + 21 = 32 + 16x

9x + 21 = 32

9x = 32 - 21

9x = 11

x = 11/9

7x+21= 16x+32

- 7x + 21 = 32 + 16x

9x + 21 = 32

9x = 32 - 21

9x = 11

x = 11/9

Added 10/10/2015 1:25:29 PM

This answer has been confirmed as correct and helpful.

Whats the young girls name who inspiration for lewis carroll's book alice in the wonderland?

Question

Updated 8/23/2016 5:53:18 AM

1 Answer/Comment

Simplify the given equation.
6 - (3x + 10) + 4(2 - x) = 15
4 - 7x = 15
4 - 4x = 15
12 - 7x = 15 User: Simplify the given equation.
5x + 2(x - 3) = -2(x - 1)
A.7x - 6 = -2x - 2
B.7x - 6 = -2x + 2
C.7x - 3 = -2x - 1 **Weegy:**
5x + 2(x - 3) = -2(x - 1)
5x + 2x - 6 = -2x + 2
7x - 6 = -2x + 2
**User:** Solve for x.
8(x + 1) - 3(x + 4) = 7(2 - x) (More)

Question

Updated 11/23/2017 9:28:02 AM

2 Answers/Comments

6 - (3x + 10) + 4(2 - x) = 15 is simplified into **-7x + 4 = 15**.

6 - (3x + 10) + 4(2 - x) = 15

6 - 3x - 10 + 8 - 4x = 15

-7x + 4 = 15

-7x = 15 - 4

-7x = 11

x = 11/-7

x = -11/7

6 - (3x + 10) + 4(2 - x) = 15

6 - 3x - 10 + 8 - 4x = 15

-7x + 4 = 15

-7x = 15 - 4

-7x = 11

x = 11/-7

x = -11/7

Added 11/23/2017 9:27:04 AM

This answer has been confirmed as correct and helpful.

8(x + 1) - 3(x + 4) = 7(2 - x)

8x + 8 - 3x - 12 = 14 - 7x

5x - 4 = 14 - 7x

5x + 7x = 14 + 4

12x = 18

x = 18/12

x = 3/2

8x + 8 - 3x - 12 = 14 - 7x

5x - 4 = 14 - 7x

5x + 7x = 14 + 4

12x = 18

x = 18/12

x = 3/2

Added 11/23/2017 9:28:02 AM

This answer has been confirmed as correct and helpful.

What is the dictionary meaning of connotation?

Question

Updated 1/16/2015 12:52:48 PM

1 Answer/Comment

32,008,745

questions answered

There are no comments.